Equivalence of Islamic Financial Literation Index with Islamic Financial Inclusion Index in The Islamic Banking Sector: A Case Study of DIY Society - Miftakhul Khasanah (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2019)
Abstract: The purpose of this research is to find out and analyse the relationship between the Islamic financial literacy index and the Islamic financial inclusion index of the DIY community in the Islamic banking sector. The research uses descriptive quantitative methods. Data collection was carried out by distributing 663 questionnaires in the DIY province. The calculation of the index of Islamic financial literacy and inclusion was carried out by referring to the OJK calculation and Sharma method. From the results of the calculation of the Islamic financial literacy index in DIY Province, the results were 32.47% while the Islamic financial literacy index, specifically for the Islamic banking sector was 26.15%. This result is much higher than the calculation of the Islamic financial literacy index conducted by OJK in 2016. Financial literacy is closely related to financial inclusion so that there needs to be conformity and continuity between both of them. Achievement of financial literacy and inclusion strategies will be more efficient if carried out together so that the achievement of public access to the financial services sector can be done more optimally and can utilise financial products and services that are suitable to achieve sustainable economic prosperity.Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui dan menganalisis keterkaitan antara indeks literasi keuangan syariah dan indeks inklusi keuangan syariah masyarakat DIY pada sektor perbankan Syariah. Penelitian menggunakan metode kuantitatif deskriptif. Pengumpulan data dilakukan dengan menyebarkan kuisioner di propinsi DIY. Perhitungan indeks literasi dan inklusi keuangan syariah dilakukan dengan merujuk pada perhitungan OJK dan metode Sharma. Dari hasil perhitungan indeks literasi keuangan Syariah di Propinsi DIY didapatkan hasil sebesar 32,47% sedangkan indeks literasi keuangan Syariah khusus untuk sektor perbankan syariah adalah 26,15%. Hasil ini jauh lebih tinggi daripada perhitungan indeks literasi keuangan syariah yang dilakukan OJK di DIY pada tahun 2016. Pencapaian strategi literasi dan inklusi keuangan akan lebih efisien jika dilakukan secara bersama-sama sehingga pencapaian akses masyarakat ke sektor jasa keuangan dapat dilakukan dengan lebih optimal dan dapat memanfaatkan produk dan layanan jasa keuangan yang sesuai untuk mencapai kesejahteraan keuangan yang berkelanjutan.